The sound of medieval song: ornamentation and vocal style according to the treatises - McGee, Timothy J. (Oxford Clarendon Press, 1998)
The Sound of Medieval Song is a study of how both sacred and secular music were actually sung during the Middle Ages. The source of the information is the actual notation in the early manuscripts as well as statements found in approximately 50 theoretical treatises written between the years 600-1500. The writings describe various singing practices and both desirable and undesirable vocal techniques, providing a fairly accurate picture of how singers approached the music of the period.